2007
DOI: 10.1007/s11664-007-0164-y
|View full text |Cite
|
Sign up to set email alerts
|

Component Overpressure Growth and Characterization of High-Resistivity CdTe Crystals for Radiation Detectors

Abstract: Spectrometer-grade CdTe single crystals with resistivities higher than 10 9 X cm have been grown by the modified Bridgman method using zone-refined precursor materials (Cd and Te) under a Cd overpressure. The grown CdTe crystals had good charge-transport properties (ls e = 2 · 10 -3 cm 2 V -1 , ls h = 8 · 10 -5 cm 2 V -1 ) and significantly reduced Te precipitates compared with crystals grown without Cd overpressure. The crystal growth conditions for the Bridgman system were optimized by computer modeling and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…[3][4][5][6] Recently, high-resistivity (>10 9 X cm), spectrometer-grade CdTe single crystals have been grown by a modified Bridgman method from zone-refined precursor materials under Cd overpressure. 7 This method produced a three-to fourfold decrease in Te precipitates compared with crystals grown without Cd overpressure.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] Recently, high-resistivity (>10 9 X cm), spectrometer-grade CdTe single crystals have been grown by a modified Bridgman method from zone-refined precursor materials under Cd overpressure. 7 This method produced a three-to fourfold decrease in Te precipitates compared with crystals grown without Cd overpressure.…”
Section: Introductionmentioning
confidence: 99%
“…The reduction in transmittance observed in CdTe crystals corresponds to absorption by Te precipitates and they are also detrimental to a number of optical, electro-optical, and liquid phase epitaxy HgCdTe substrate applications [11][12][13][14][15]. In order to control Te precipitation and eliminate Te precipitates, numerous studies of growth techniques [1,[16][17][18][19][20][21], thermodynamic calculations of phase diagrams [22][23][24][25], thermodynamic calculations of kinetic properties of point defects [25][26][27][28], and modeling of solidification [29,30] and Te precipitation [31] have been attempted. However, there has been less emphasis in predicting the kinetics of Te precipitation during crystal growth and annealing, where knowledge of Te precipitation kinetics will be helpful in guiding process development.…”
Section: Introductionmentioning
confidence: 99%
“…CdTe nanoparticles (NPs) exhibit interesting physical properties such as large excitation Bohr radius, narrow emission band, and high photoluminescence . These properties make them attractive in a variety of applications, such as light emitting diodes, silver ions detectors, biological labels, and solar cells. Thin CdTe films play a significant role as IR and γ detectors; in solar cells, X-ray imaging in dentistry, and mammography; and are used as substrates for the epitaxial growth of Hg-based semiconductors. …”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Thin CdTe films play a significant role as IR and γ detectors; in solar cells, X-ray imaging in dentistry, and mammography; and are used as substrates for the epitaxial growth of Hg-based semiconductors. [6][7][8][9][10][11] Several studies aimed at implanting gold or silver ions or metals into CdTe and other semiconductor surfaces for two main reasons: (i) creating an ohmic contact 10,12,13 and (ii) as an anchor point for attaching other species, such as organic molecules. 14 Different mechanisms were proposed for the reaction between these metal ions and CdTe or CdSe; 4,10,12,[14][15][16][17][18][19] for example, Wang et al 4 and Gheorghita et al, 10 who studied the reaction between silver ions and thin CdTe films, suggested that some of the Cd ions were replaced by silver ions, thus changing the electrical and optical properties of the semiconductor.…”
Section: Introductionmentioning
confidence: 99%